EVALUATE CLINICAL JUDGEMENT AMONG NURSES IN PUBLIC HOSPITAL, MALAYSIA USING SBARE TOOL: A QUALITATIVE RESEARCH - Azliha Minai Rajab (Yayasan Pendidikan Medika Indonesia, 2023)
This study highlights the importance of effective communication in healthcare, particularly during patient transitions among healthcare professionals. To address communication inefficiencies during these transitions, the structured communication tool SBARe (Situation, Background, Assessment, Recommendation, and Evaluation) is introduced among nurses in public hospitals. The methodology involves a narrative approach using in-depth interviews (IDI) and thematic analysis to analyze data. The study's findings identify three main themes: positive perceptions of the SBARe format in patient transition reports, with sub-themes on clarity and simplicity of the format; the applicability of SBARe in daily routines with improved document reporting quality and the evaluation element; and the positive impact of SBARe on communication, knowledge, and willingness to apply it in patient care practices, with sub-themes of enhanced effective communication, increased knowledge, and readiness for SBARe implementation. In conclusion, the use of SBARe yields positive participant views on its effectiveness and utility in daily healthcare practices, emphasizing the crucial role of effective communication in healthcare and suggesting potential for broader implementation in the healthcare domain as a whole.